2015
DOI: 10.1088/1748-9326/10/10/105003
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation fires, absorbing aerosols and smoke plume characteristics in diverse biomass burning regions of Asia

Abstract: In this study, we explored the relationships between the satellite-retrieved fire counts (FC), fire radiative power (FRP) and aerosol indices using multi-satellite datasets at a daily time-step covering ten different biomass burning regions in Asia. We first assessed the variations in MODIS-retrieved aerosol optical depths (AOD's) in agriculture, forests, plantation and peat land burning regions and then used MODIS FC and FRP (hereafter FC/FRP) to explain the variations in AOD characteristics. Results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 56 publications
4
45
0
Order By: Relevance
“…As Schreier et al () demonstrated, woody savanna and cropland fires have a relatively higher NO x Ce than forest fires, and this could result from woody savanna and cropland biomes having higher N content than forests, providing more N content to be oxidized into NO x . Meanwhile, for smoke aerosols, Vadrevu et al () pointed out that forest fires emitted more absorptive aerosols than cropland. Differences among fires in the current work showed good consistencies with their descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…As Schreier et al () demonstrated, woody savanna and cropland fires have a relatively higher NO x Ce than forest fires, and this could result from woody savanna and cropland biomes having higher N content than forests, providing more N content to be oxidized into NO x . Meanwhile, for smoke aerosols, Vadrevu et al () pointed out that forest fires emitted more absorptive aerosols than cropland. Differences among fires in the current work showed good consistencies with their descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Their definition is comparable to our CALIOP median plume height, which produced a value of 2.3±0.7 km for the September months. Other CALIOP smoke plume heights have been reported over eastern Europe (1.7-6 km) and several regions and biomes across Asia (0.8-5.3 km) (Amiridis et al, 2010;Labonne et al, 2007;Tosca et al, 2011;Vadrevu et al, 2015).…”
Section: Caliop Smoke Plume Observationsmentioning
confidence: 92%
“…9 in Schreier et al (2014) and Fig. 13 in van der Werf et al (2010), the soil for IND is supposed to be mainly composed of cropland (agriculture), which is associated with an EF CO of 102 ± 33 g kg −1 , and probably also by extratropical forest, which is characterized by an EF CO equal to 122 ± 44 g kg −1 , and savanna, with an EF CO of 63 ± 17 g kg −1 . The fuel type for SEA is supposed to be a mix of extratropical forest and savanna, with an EF CO of 122 ± 44 and 63 ± 17 g kg −1 , respectively.…”
Section: Analysis Based On the Type Of Vegetationmentioning
confidence: 99%
“…This is strongly possible as agricultural residue burning is prevalent in these regions (e.g., Kaskaoutis et al, 2014;Vadrevu et al, 2015). Over India and over Southeast Asia, our ER (HCOOH/CO) values (6.8 × 10 −3 ± 0.44 × 10 −3 mol mol −1 for India and 5.8 × 10 −3 ± 0.15 × 10 −3 mol mol −1 for Southeast Asia) are close to the value referenced by Akagi et al (2011) for cropland fires (6 × 10 −3 mol mol −1 ).…”
Section: Analysis Based On the Type Of Vegetationmentioning
confidence: 99%